PERSEPSI MASYARAKAT DESA NUSAPATI TENTANG HUTAN RAKYAT DALAM PENGELOLAAN LAHAN KABUPATEN MEMPAWAH - ., syarifah; roslinda, emi; ekyastuti, wiwik (Universitas Tanjungpura, 2016)
Land management refers to land use activities by local community in order to meet the necessities of life. The aim of this study to reveal the management model in Nusapati and its services and to find out about public perception of the different models for land management such as forests, community forests, gardens and rice fields. The research was conducted from May to June 2016 through field observation with a Focus Group Discussion (FGD) using research tools such as interview guides. The results show that the four models of the land are used for subsistence either directly (economic and social purposes) or indirectly (ecological). Respondents prefer the garden as a model of the most important land with a score of 34%, followed by community forest with a score of 25% third after community forest is rice field with a score of 23% and finally is a forest with a score of 18%. The results of the analysis show that the average public is it the institution, age, education, and gender has no differences on the model of land that is important to meet their needs. Meanwhile, the community forest is not necessarily considered to meet the daily need given the harvest time is quite long. The plant species that exist in the community lands are quite varied so as to provide considerable benefits for the community and the environment.Â Keywords: community, community forest, Land management.